Differential Membrane Localization and Intermolecular Associations of α-Dystrobrevin Isoforms in Skeletal Muscle - Peters, Matthew F. (The Rockefeller University Press, 1998)
α-Dystrobrevin is both a dystrophin homologue and a component of the dystrophin protein complex. Alternative splicing yields five forms, of which two predominate in skeletal muscle: full-length α-dystrobrevin-1 (84 kD), and COOH-terminal truncated α-dystrobrevin-2 (65 kD). Using isoform-specific antibodies, we find that α-dystrobrevin-2 is localized on the sarcolemma and at the neuromuscular synapse, where, like dystrophin, it is most concentrated in the depths of the postjunctional folds. α-Dystrobrevin-2 preferentially copurifies with dystrophin from muscle extracts. In contrast, α-dystrobrevin-1 is more highly restricted to the synapse, like the dystrophin homologue utrophin, and preferentially copurifies with utrophin. In yeast two-hybrid experiments and coimmunoprecipitation of in vitro–translated proteins, α-dystrobrevin-2 binds dystrophin, whereas α-dystrobrevin-1 binds both dystrophin and utrophin. α-Dystrobrevin-2 was lost from the nonsynaptic sarcolemma of dystrophin-deficient mdx mice, but was retained on the perisynaptic sarcolemma even in mice lacking both utrophin and dystrophin. In contrast, α-dystrobrevin-1 remained synaptically localized in mdx and utrophin-negative muscle, but was absent in double mutants. Thus, the distinct distributions of α-dystrobrevin-1 and -2 can be partly explained by specific associations with utrophin and dystrophin, but other factors are also involved. These results show that alternative splicing confers distinct properties of association on the α-dystrobrevins.